Questioning assessment - Joanne Berry; Rhian Ellis; Patricia Xavier (Journal of Learning Development in Higher Education)
This brief communication offers a summary of our experience of holding a series of university-wide online discussions which explored and questioned the many assumptions we bring to assessment practices in higher education. It aims to demonstrate the value of such discussions, highlighting key lessons we learned, what they suggest for the future of assessment, and how we can better understand and support our students with the benefit of insights gained. Finally, we offer some practical tips for fellow higher education professionals new to this format, based on what worked well for us.